L-Isoleucine derived bifunctional phosphine catalyses asymmetric [3 + 2]-annulation of allenyl-esters and -ketones with ketimines. Issue 61 (13th June 2016) - Sankar, Muthukumar G.; Garcia-Castro, Miguel; Golz, Christopher; Strohmann, Carsten; Kumar, Kamal
Abstract : l -Isoleucine derived bifunctional N -acylaminophosphine catalyzed a [3 + 2]-annulation reaction between allenyl carbonyl compounds and isatinimines to afford a facile and asymmetric access to 3, 2′-dihydropyrrolyl spirooxindoles. Abstract : The zwitterionic 1, 3-dipoles generated by the addition of a bifunctionall -isoleucine derived N -acylaminophosphine to allenic esters as well as ketones were successfully trapped with isatin derived ketimines in a [3 + 2]-annulation reaction to deliver 3, 2′-dihydropyrrolyl spirooxindoles in high yields (up to 88%) and with excellent enantioselectivities (up to >99%). The asymmetric annulation reaction provides a facile access to biologically relevant small molecules embodying the natural product spirocyclic core.